Designing smart objects in everyday life : intelligences, agencies, ecologies - Rozendaal, Marco C.; Marenko, Betti; Odom, William (Designer) (London ; New York : Bloomsbury Visual Arts, 2021)
"The dramatic acceleration of digital technologies and their integration into physical products is transforming everyday objects. Such objects are increasingly capable of interacting with humans in a purposeful and intelligent manner. This book offers a critical assessment on smart design, together with methods and tools to deal with the challenges and opportunities presented. If design is concerned with creating purposeful interventions in everyday life, then how would the design of smart objects change to account for the animation and the 'personality' projected by the users? What range of competences, skills and expertise are needed to design smart objects in the everyday life?"--
An illustrated field guide to fungal AI for designers / David Kirk, Effie Le Moignan and David Verweij -- Dramaturgy for devices : theatre as perspective on the design of smart objects / Maaike Bleeker, Marck C. Rozendaal.
"This book is largely the result of an interdisciplinary workshop that was held at the Lorentz Center, University of Leiden, The Netherlands from the 30th of April to May 4th 2018"--Introduction.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Internet of things; Cooperating objects (Computer systems)